Development of a Didactic Workbench Using Real-Time Monitoring System for Teaching of Photovoltaic Systems - Silva, Sérgio A. Oliveira da (2018)
This paper presents the deployment of a didactic workbench intended to support theoretical and practical studies addressed in subjects of undergraduate and postgraduate electrical engineering courses involving photovoltaic (PV) systems. The proposed system operates in real-time and is composed of a computational graphic interface operating in conjunction with a double-stage PV system connected to the power grid. Besides the PV array, the PV system consists of a step-up DC-DC converter, intended to track the maximum power point, and a current-controlled full-bridge inverter, intended to inject the energy produced by the PV array into the grid. The monitoring system allows to perform the following tasks: i. assist the performance evaluation of maximum power point tracking techniques tied to projects; ii. visualize the measured PV array magnitudes (voltage, current and power), as well as the estimated ones calculated from the PV array mathematical model and from the real measured values of solar irradiation and temperature; iii. analyze electric power quality indicators, based on the grid voltage and current magnitudes, and others. Experimental results are presented with the objective of testing and evaluating the versatility of the proposed didactic workbench applied in an educational environment.